Business Planning bagi Mahasiswa Asrama PGSD Universitas Negeri Malang Sebagai Perwujudan Decent Work and Economic Growth of SDG’s Goals - Khusnul Khotimah; Esti Untari; Tomy Rizky Izzalqurny (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
One of the eight SDGs is decent work and economic growth. The SDG's goal can be interpreted as human welfare will be achieved if they have decent work. Based on this need, all stakeholders must be able to create the widest possible employment opportunities. To realize these ideals or goals, there needs to be participation and collaboration between institutions/sectors, including the involvement of universities. One of the roles of higher education in supporting the realization of the SDG's goals is empowering students who live in campus dormitories by providing experience (soft skills) to students in the field of edupreneurship (entrepreneurship). Therefore, assistance in preparing business planning for the State University of Malang campus dormitory students was carried out. The results obtained from this activity are that dormitory students can produce eight prospective business plans realized in the business model canvas (BMC).